1990
DOI: 10.1093/ajcp/94.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clot-Detection Methods and Reagents on Activated Partial Thromboplastin Time (APTT): Implications in Heparin Monitoring by APTT.

Abstract: Two automatic coagulometers, ACL 810 (Instrumentation Laboratory), a laser-nephelometric centrifugal analyzer, and KoaguLab 40 A (Ortho Diagnostics), an optical automatic coagulometer, were compared with the manual tilt-tube method for the performance of activated partial thromboplastin time (APTT). Seven commercial APTT reagents were used for duplicate determinations in 30 normal controls, 26 patients with liver disease, and 33 patients on full-dose heparin treatment. Clotting times were longer with the manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Specific activity is defined as activity per amount of material and, for heparins, is usually expressed in international units (IU) per mg. One milligram of a natural heparin contains an unknown amount of molecules that do not contain the AT binding pentasaccharide and therefore weight is not an exact measure of the amount of active material. The activity of any heparin relative to a standard is strongly dependent upon the test method and experimental conditions [27–29]. So neither IU nor mg can be used as units to express specific activity with high precision.…”
Section: Discussionmentioning
confidence: 99%
“…Specific activity is defined as activity per amount of material and, for heparins, is usually expressed in international units (IU) per mg. One milligram of a natural heparin contains an unknown amount of molecules that do not contain the AT binding pentasaccharide and therefore weight is not an exact measure of the amount of active material. The activity of any heparin relative to a standard is strongly dependent upon the test method and experimental conditions [27–29]. So neither IU nor mg can be used as units to express specific activity with high precision.…”
Section: Discussionmentioning
confidence: 99%
“…The results of APTTs determined for heparin dosage monitoring can be influenced by the method of end-point detection (D'Angelo et al, 1990). We have demonstrated that use of one particular coagulometer (ACL) with one reagent was not associated with differences between APTT ratio when compared to manual end-point detection , whereas with the same instrument, a significant increase in APTT ratios was obtained using another reagent (manual mean APTT ratio of patients 2´5, compared with ACL mean 3´3).…”
Section: Therapeutic Ranges Specific For Aptt Techniquementioning
confidence: 96%
“…APTT is the test most widely used to monitor heparin treatment [6, 7] and many studies have shown that it is suitable for adjusting the dose of unfractionated heparins [8, 9]. Given the known variability among APTT reagents [10, 11], we initially compared five commercial reagents in vitro and chose the reagent yielding a linear increase in clotting time over a wide range of S 18326 concentrations, leading to an increase up to 7‐fold the basal APTT (Figure 1).…”
Section: Discussionmentioning
confidence: 99%